2021
DOI: 10.1097/j.jcrs.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of once-daily and twice-daily dosing of topical bromfenac 0.09%: aqueous pharmacokinetics and clinical efficacy study

Abstract: Methods:In phase I, single-drop aqueous pharmacokinetics of topical bromfenac was estimated at 15 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 12 hours, and 24 hours using liquid chromatography mass spectrometry in 60 eyes. In phase II, 45 eyes undergoing phacoemulsification were enrolled: group I (control, n = 15), group II (once-daily bromfenac, n = 14), and group III (twice-daily bromfenac, n = 16). Intraoperative pupillary miosis, postoperative anterior chamber (AC) flare, Summed Ocular Inflammation Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, like all surgical procedures, it can carry certain risks and complications, such as corneal edema, cystoid macular edema, endophthalmitis, and retinal detachment. The FDA has approved the use of topical NSAIDs for the prevention of postoperative cystoid macular edema [ 178 ]. However, the use of pharmacological compounds as an alternative to cataract surgery remains under development.…”
Section: Nano-based Dds For Anterior Segment Diseasesmentioning
confidence: 99%
“…However, like all surgical procedures, it can carry certain risks and complications, such as corneal edema, cystoid macular edema, endophthalmitis, and retinal detachment. The FDA has approved the use of topical NSAIDs for the prevention of postoperative cystoid macular edema [ 178 ]. However, the use of pharmacological compounds as an alternative to cataract surgery remains under development.…”
Section: Nano-based Dds For Anterior Segment Diseasesmentioning
confidence: 99%
“…97 Twice daily bromfenac 0.09% does not improve postoperative flare compared to once daily dosing. 122 Flare comparisons between topical corticosteroids and NSAIDs have yielded no statistically significant differences between the following: dexamethasone versus flurbiprofen, 101 dexamethasone versus diclofenac, [102][103][104] dexamethasone versus bromfenac 105 ; bromfenac versus betamethasone 108 or bromfenac versus fluorometholone 0.1% 109 ; diclofenac versus 1% prednisolone, 123 fluorometholone/levofloxacin versus tobramycin/dexamethasone. 107 Erichsen et al found no difference in postoperative flare between those taking combination prednisolone 1%/ ketorolac 0.5% versus ketorolac 0.5% alone, 96 as did Ylinen et al with diclofenac 0.1%/dexamethasone 0.1% versus diclofenac 0.1%.…”
Section: Postoperative Regimenmentioning
confidence: 99%
“…Liquid eye drops are the most desirable dosage form to treat the local ophthalmic diseases. 6 The quick elimination in the extraocular area leads to the low bioavailability of eye drops which makes frequent instillations an often required method to get the expected therapeutic effect, and this leads to rising inconvenience and adverse effects. 7 The increase in the residence time of the drug in the precorneal area and absorption would improve its therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The ocular drug delivery system requires a series of specified characteristics according to the physiological structure of the eye. Liquid eye drops are the most desirable dosage form to treat the local ophthalmic diseases . The quick elimination in the extraocular area leads to the low bioavailability of eye drops which makes frequent instillations an often required method to get the expected therapeutic effect, and this leads to rising inconvenience and adverse effects .…”
Section: Introductionmentioning
confidence: 99%